Effect of anemia in pregnant women on the incidence of premature labor and low birth weight - Akib, Asridawati; Rukinah, Rukinah; Limbong, Theresia (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: Anemia in pregnant women is one of the health problems that often occur and can have a negative impact on pregnancy. Iron and other nutrient deficiencies during pregnancy can increase the risk of complications, including premature labor and low birth weight (BBLR). This study aims to analyze the effect of anemia in pregnant women on premature labor and BBLR incidence. Research Methodology: This study uses an observational design with a retrospective cohort approach. Data is collected from the medical records of pregnant women who have given birth in the hospital for a certain period. The research sample consisted of pregnant women who experienced anemia and those who did not experience anemia. Result: The results showed that pregnant women with anemia had a higher risk of preterm labor compared to pregnant women without anemia (OR = 2.5; p < 0.05). In addition, the prevalence of babies with low birth weight was higher in mothers with anemia (OR = 3.1; p < 0.05). The results of the multivariate analysis showed that anemia in pregnant women was an independent risk factor for the incidence of premature labor and BBLR after being controlled by other factors such as maternal age, nutritional status, and obstetric history. Conclusion: Anemia in pregnant women has a significant effect on the increased risk of premature labor and low birth weight. Therefore, efforts to prevent and treat anemia during pregnancy must be improved through early screening, nutrition education, and iron and folic acid supplementation to reduce adverse impacts on mothers and babies